The effectiveness of using poetry writing activities to teach parts of speech in Malaysian secondary language classroom / Gloria Eve Jikim - Jikim, Gloria Eve (Faculty of Education, 2014)
English language is very important in our lives. The process of globalization that is occurring now has made it a requirement to master this language to enable mankind to advance and gain more knowledge and information from other parts of the globe. However, many have not mastered the language despite the measures taken by the government to introduce the language to students since primary school years up until tertiary education. The most important item that they have not mastered is the knowledge on grammar item, the parts of speech. Thus the main aim of this study was to determine the effectiveness of using poetry writing activities to teach parts of speech in Malaysian Secondary Language Classroom. It also aims to seek the various effective approaches and strategies to teach parts of speech. The subjects for this study involved 71 Form 1 students from SMK Kota Kemuning, Shah Alam. Two teachers were also observed during the execution of poetry writing lessons. Pre-test and post test on parts of speech knowledge were also conducted prior and after the execution of poetry writing classes. The findings of the study revealed that there was a slight improvement in subjects’ post-test result after they were exposed to poetry writing activities. It was later discovered that poetry writing activities assisted students’ understanding on parts of speech.